Ablation behavior of boron-modified phenolic resin irradiated by high-energy continuous-wave laser and its evolution of carbon structure. (15th October 2019) - Ma, Chen; Ma, Zhuang; Gao, Lihong; Liu, Yanbo; Wu, Taotao; Wang, Fuchi; Ishida, Hatsuo
Abstract: Despite many years of use of boron-modified phenolic resin (BPF) in the aerospace and auto industry, it is still unknown if such resin can be used in extreme environments, especially under exposure to high energy continuous-wave (CW) laser that can totally destroy many traditional materials in several seconds. Compression molded BPF plates are tested with high energy CW laser to study the laser ablation behavior. Results reveal that the laser parameters including irradiation time and laser power density have a great effect on the ablation morphology and mass ablation rate. BPF keeps decomposing into residual char due to the high temperature caused by laser. The graphite structure of residual char is gradually improved during laser irradiation, resulting in improved thermal stability of residual char. In addition, the micro-morphologies reveal that the residual char possess porous structure which leads to the thermal insulation property and minimizes the ablation damage propagating into the BPF bulk. Both the improved thermal stability and the thermal insulation property of the residual char can mitigate the ablation damage caused by the high energy CW laser. Graphical abstract: Unlabelled Image Highlights: Laser ablation behavior of boron-modified phenolic resin was first proposed. The degree of graphitization of the formed residual char was demonstrated to keep increasing during laser ablation. The porous structure of residual char is proved to be the key factor leading to the thermal insulation property. The reason why boron-modified phenolic resin owns excellent laser ablation resistance is clearly proposed.